Peningkatan Visibilitas Digital melalui Implementasi Search Engine Optimization (SEO) di PT. Olean Permata Telematika - Achmad Zakki Falani; I Putu Artaya; Latipah; Lukman Junaedi (Universitas Merdeka Surabaya, 2026)
Digital transformation has encouraged Internet Service Provider (ISP) companies to optimize digital media as a strategic tool for marketing and customer communication. One of the major challenges faced is the low visibility of company websites on search engines, which limits public access to information regarding services offered. This activity aims to enhance the digital visibility of PT Olean Permata Telematika through the implementation of Search Engine Optimization (SEO) strategies. The methods employed include an initial website analysis, technical and content optimization, as well as training and mentoring for company personnel on sustainable SEO practices. The results indicate an improvement in website visibility on search engine results and an increased level of understanding among the partner regarding SEO implementation. This activity is expected to strengthen the company’s digital marketing strategy and improve its competitiveness in the ISP industry.